2021
DOI: 10.1088/1757-899x/1175/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Safe distance reminder system on ship against port for the standing process using image processing

Abstract: Since ancient times, Indonesia has been known as a country that conducts trading activities. However, the number of accidents when the ship is about to dock is an indication of the need to improve the marine transportation system. The factors that cause accidents include human, technical and weather errors. Seeing these conditions and also related to the increasingly rapid development of technology, modern solutions for detecting objects using cameras can be developed. By using a PC as a video processor from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The experimental results showed that this algorithm has higher detection accuracy than the traditional SSD algorithm and increases the detection ability of small objects. Santosa et al [103] proposed an improved SSD algorithm with MobileNet as the backbone to classify the ship and transmit the signal to the engine to control the engine shutdown action, effectively avoiding accidents during the ship docking process.…”
Section: Single Shot Multi-box Detector (Ssd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that this algorithm has higher detection accuracy than the traditional SSD algorithm and increases the detection ability of small objects. Santosa et al [103] proposed an improved SSD algorithm with MobileNet as the backbone to classify the ship and transmit the signal to the engine to control the engine shutdown action, effectively avoiding accidents during the ship docking process.…”
Section: Single Shot Multi-box Detector (Ssd)mentioning
confidence: 99%
“…Santosa et al. [103] proposed an improved SSD algorithm with MobileNet as the backbone to classify the ship and transmit the signal to the engine to control the engine shutdown action, effectively avoiding accidents during the ship docking process.…”
Section: Deep Learning For Object Detectionmentioning
confidence: 99%